Successful treatment of severe refractory autoimmune hemolytic anemia after hematopoietic stem cell transplant with abatacept. Issue 9 (4th September 2018) - Hess, Jennifer; Su, Leon; Nizzi, Frank; Beebe, Kristen; Magee, Kyrie; Salzberg, Dana; Stahlecker, Jennifer; Miller, Holly K.; Adams, Roberta H.; Ngwube, Alexander
Abstract : BACKGROUND: After hematopoietic stem cell transplantation (HSCT) autoimmune hemolytic anemia (AIHA) is a known and fairly common complication. It is often refractory to conventional therapies including corticosteroids, intravenous immunoglobulin, splenectomy, and the more recently described use of monoclonal antibodies. The high morbidity associated with these severe persistent cases elucidates the gaps in alternative therapies available for treatment. STUDY DESIGN AND METHODS: We described the successful use of abatacept for severe refractory AIHA after HSCT in three patients. RESULTS: Three pediatric patients with refractory AIHA after allogeneic stem cell transplantation were observed to be unresponsive to multitude immunosuppressive therapies, resulting in persistent transfusion dependency. Treatment with abatacept, a fusion protein that inhibits T‐cell activation by binding to CD80/CD86 on antigen‐presenting cells (APCs), thus blocking the required CD28 interaction between APCs and T cells, resulted in the resolution of hemolysis. CONCLUSION: Abatacept may provide significant clinical benefit in the management of AIHA after HSCT.